Penguatan Karakter Islami Anak Berbasis Orientasi Pendidikan dalam Tafsir Al-Qurṭubī: Implementasi Model Pembelajaran Tilāwah, Tazkiyah, Ta’līm, dan ‘Ibādah di Mdtu Al-Munawarah Pekanbaru - Hidayatullah Isma’il; Ilham Abiyusuf; Fadhli Ihsan; Pakhrurrozi Pakhrurrozi; Muhammad Althafullayya; Azra Rahmi; Selfa Ummi (Altifani : Jurnal Pengabdian Masyarakat Ushuluddin, Adab, dan Dakwah, 2026)
Contemporary Islamic education faces a dichotomy between cognitive and spiritual intelligence, leading to a character crisis. This study aims to reconstruct an integrative Islamic education paradigm based on al-Qurṭubī’s interpretation of Surah al-Jumu‘ah verses 1–11. This qualitative library research employs tafsīr tahlīlī (analytical) and maudhū‘ī (thematic) approaches, using al-Jāmi‘ li Aḥkām al-Qur’ān as the primary source. Data analysis proceeded through three stages: data inventory, thematic grouping into four educational pillars (tilāwah, tazkiyah, ta‘līm, ‘ibādah), and interpretive synthesis of linguistic meanings, asbāb al-nuzūl, and legal istinbāṭ. The findings reveal that al-Qurṭubī views tilāwah as transformative reception of revelation; tazkiyah as purification of the soul from unbelief and sins, serving as a prerequisite for meaningful knowledge; ta‘līm al-kitāb wa al-ḥikmah as the integration of knowledge transfer and value internalization; and ‘ibādah as a practical culmination that tests priority, discipline, and life balance. Al-Qurṭubī’s critique of the parable of the donkey carrying books and the incident of companions leaving the sermon for trade affirms that education without tazkiyah produces empty formalism. In conclusion, al-Qurṭubī’s exegesis offers a holistic educational system unifying cognitive, affective, psychomotor, and social dimensions to address the contemporary moral crisis